SOSIALISASI LATIHAN PENCATATAN KEUANGAN SEDERHANA PADA PEDAGANG TOKO KELONTONG DI SAMARINDA - Sri Wahyuti; Priscilla Sherli Tani; Nur Anggi Andini (Wadah Inovasi Indonesia, 2022)
This program aims to provide outreach training, particularly to teach Peek MSME actors straightforward financial documentation skills. MSME actors now have a better understanding of how to manage financial records, enabling them to manage company finances more effectively. The training activities make use of outreach strategies and practices. As a result of this training, peep show business actors are better able to keep basic financial recordsfinancial documentation skills. MSME actors now have a better understanding of how to manage financial records, enabling them to manage company finances more effectively. The training activities make use of outreach strategies and practices. As a result of this training, peep show business actors are better able to keep basic financial records. The fundamental issue that MSME players face is that they never record financial transactions in a straightforward and chronological manner, making it impossible to assess a company's financial health or expansion. It is anticipated that this practicum will enhance comprehension and knowledge.